Kajian Urgensi Kemitraan Publik Swasta di Kota Palembang (Universitas 17 Agustus 1945 Surabaya, 2022)
The desire of the Palembang City government to work on colorful systems with Public Private hookups (PPP) medium, driven by limited backing sources, mortal coffers, technological capabilities and so forth. This case do for realizing the